IMPLEMENTATION OF GOOD GOVERNANCE IN THE PROCUREMENT OF GOODS AND SERVICES TO ANTICIPATE STATE FINANCIAL LOSSES - Pandi Harahap, Ahmad Ari; Triono Eddy; Ida Hanifah (Faculty of Law, Universitas Pekalongan, 2024)
Procurement of government goods and services is one of the activities that is very prone to corruption, collusion, and nepotism (KKN). In addition to carrying out law enforcement, to overcome KKN in the procurement of goods and services, various supporting policies are established that are enforcement and prevention. The research conducted is normative juridical or research that analyzes written law, jurisprudence, and norms that live in society. The descriptive-analytical approach aims to take systematic, factual, and accurate data on a problem based on applicable laws and legal norms. The results of this study show that Good Governance can anticipate state financial losses in the Government BJP through the implementation of the principles of participation, rule of law, transparency, effectiveness and efficiency, and accountability. The forms of policies in the procurement of fair goods and services are the establishment of integrity pacts by both relevant agencies and PJB participants, the E-procurement System, the procurement of goods and services through electronic tenders that are spared, and a comprehensive audit system to find indications of violations.Keywords: Good Governance, Goods and Services, State Finance, E-Governance, E-Procurement.